Beyond the blue banana? Structural change in Europe's geo-economy - Gert-Jan Hospers (European Regional Science Association (ERSA), 2002)
For centuries, the so-called 'Blue Banana' has shown the greatest development potential in Europe's geo-economy. This metropolitan area, extending from the north-west of London through Germany to Milan, traditionally has been a breeding place for entrepreneurship and innovation in Europe. Recently, however, commentators have identified the 'Sunbelt' from Milan to Valencia and - anticipating the coming enlargement of the European Union - the 'Yellow Banana' from Paris to Warsaw as the growth poles of the future. Ultimately, it is claimed, these emerging centres of gravity may even take over the dominant position of the Blue Banana in the European economy. In this paper we explore the question how likely it is that the contemporary structure of Europe's economic-geographical system is really changing in the next decades. After a short discussion of the 'stylized facts' of unbalanced growth in Europe we develop a framework in which insights from structural change theory and economic geography are combined. In particular, we link the literature on sectoral changes from industry to services in time with spatial concepts such as urbanization economies, institutional inertia and geographical path dependency. With the help of this framework it is argued that over time the techno-economic and institutional structure of specialized regions may become locked-in into rigid trajectories. Simultaneously, we suggest that regions with sectoral diversity provide the flexibility which is needed to absorb new techno-economic developments and to develop 'new combinations'. This framework of structural change in time and space is applied to the European context. We find that it is particularly the Blue Banana that may face a favourable future. The fact is that thanks to its diversified structure this area rather than the Sunbelt and the Yellow Banana can build on strong urbanization economies. Therefore, we expect that the Blue Banana despite its industrial tradition continues to be the major economic growth axis in the European service economy. In this line of reasoning, also European structural policy may take on a different aspect: rather than aiming for regional balance the policy objective might be striving for an optimal economic, institutional and infrastructural connection of less developed regions to the Blue Banana. In this way, spread effects from cities in the Blue Banana to connected areas are facilitated, which ultimately may contribute to a less unbalanced growth of Europe's geo-economy.
Keywords: 330